Move-step structures of literature Ph.D. theses in the Japanese and UK higher education - Ono, Masumi (Journal of Writing Research, 2017)
This study investigates the move-step structures of Japanese and English introductory chapters of literature Ph.D. theses and perceptions of Ph.D. supervisors in the Japanese and UK higher education contexts. In this study, 51 Japanese and 48 English introductory chapters of literature Ph.D. theses written by first language writers of Japanese or English were collected from three Japanese and three British universities. Genre analysis of 99 introductory chapters was conducted using a revised “Create a Research Space” (CARS) model (Swales, 1990, 2004). Semi-structured interviews were also carried out with seven Japanese supervisors and ten British supervisors. The findings showed that the introductory chapters of literature Ph.D. theses had 13 move-specific steps and five move-independent steps, each of which presented different cyclical patterns, indicating cross-cultural similarities and differences between the two language groups. The perceptions of supervisors varied in terms of the importance and the sequence of individual steps in the introductory chapters. Based on the textual and interview analyses, a discipline-oriented Open-CARS model is proposed for pedagogical purposes of teaching and writing about this genre in Japanese or English in the field of literature and related fields.